A microcrack strain sensor and its preparation method

By forming a brittle conductive film on the flexible base layer and creating microcracks, the problem of easy failure of microcrack strain sensors in the prior art under large strain is solved, and a strain sensor with efficient sensing under low strain and good stability is achieved.

CN114941980BActive Publication Date: 2025-03-25ZHONGSHAN WANGCAI TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210527434.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-16
Publication Date
2025-03-25
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

Existing microcrack strain sensors are prone to irreversible damage under large strains, making it difficult to adapt to complex practical application environments.

Method used

Using a combined structure of a flexible base layer and a brittle conductive film crack layer, the strain sensing performance is improved by forming a brittle conductive film on the flexible base layer and producing uniform microcracks.

Benefits of technology

It achieves excellent strain sensing performance under low strain and maintains good sensing performance after large strain or cyclic strain, which is suitable for complex practical application environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114941980B_ABST
    Figure CN114941980B_ABST
Patent Text Reader

Abstract

The present invention discloses a microcrack strain sensor and a preparation method thereof. The microcrack strain sensor comprises a flexible substrate layer, a brittle conductive film crack layer, and a flexible packaging layer stacked in sequence from bottom to top, and an electrode is introduced to realize electrical signal output. The prepared brittle conductive film is coated on the flexible substrate layer, and microcracks are formed by pre-bending or stretching. The microcrack strain sensor is based on the strong interaction between the brittle conductive film crack layer and the flexible substrate layer. The brittle conductive film crack layer is divided into a transition layer close to the flexible substrate layer and a main body layer away from the flexible substrate layer. Under various strains such as stretching, bending, and contact pressure, the transition layer and the main body layer present different crack extension morphologies. A huge change in resistance value (>50,000 times) can be achieved under a relatively small strain (<20%), and it has extremely excellent strain sensing performance. This method of constructing a microcrack strain sensor is called the Chen‑Gong model.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible electronic devices, and specifically relates to a micro-crack strain sensor and a preparation method thereof, and in particular to a micro-crack strain sensor based on a flexible substrate layer-brittle conductive layer and a preparation method thereof. Background Art

[0002] In the fields of wearable smart devices, implantable electronic devices, and intelligent robots, flexible strain sensors are one of the most important devices; they can convert strain into electrical signals and further convert them into digital signal outputs. Compared with traditional hard sensors made of metals or semiconductors, flexible strain sensors can change their shapes arbitrarily and fit anywhere on the surface of the skin or the surface of intelligent robots, so the application environment of flexible strain sensors is wider. In addition, the strain response range and GF value (the resistance change rate under unit strain, often used as one of the criteria for evaluating strain sensing performance) of flexible strain sensors are better than those of traditional hard sensors. Therefore, there has been an endless stream of research on flexible strain sensors in recent years. Among them, the most common method for preparing flexible strain sensors is to evenly blend a flexible polymer matrix with a conductive filler, and the conductive filler forms a conductive path in the flexible polymer matrix. When the composite material is strained, the conductive path is destroyed, and the resistance of the composite material rises sharply, so it has better strain sensing performance. However, the flexible strain sensors prepared in this way usually need to have a higher GF value (5-500) under a larger strain (>100%).

[0003] Patent CN 113930037 A modifies nanometal / graphene by grafting amino groups on its surface, and the amino groups undergo condensation reaction with the carboxyl groups in the matrix-modified polyvinyl alcohol. This method improves the dispersion of nanometal / graphene in the modified polyvinyl alcohol matrix, and the evenly dispersed conductive filler network is more easily destroyed in strain, so the composite material has good strain sensing performance (GF value is about 7 at 80% strain). At the same time, the chemical bonding between the conductive filler and the polymer matrix makes the composite material have good stability and fatigue resistance during cyclic stretching. However, in actual application, strain sensors are often required to generate sufficiently large signals for more subtle strains, which is unattainable by strain sensors of conductive composite materials.

[0004] Inspired by the weak signals from spider webs that spider legs can sense, scientists have designed strain sensors with microcrack structures in recent years, that is, sputtering or spraying a layer of nano-scale metal film on the surface of a flexible base layer, and bending or stretching the metal film to form uniform microcracks on the surface. During the stretching process, the expansion of the metal film microcracks will cause the thickness of the metal film at the crack to decrease, thereby causing the resistance of the strain sensor to increase sharply. The GF value at extremely low strain (<5%) can be as high as (2000-80000). Patent CN 113310395 A places a coating template with a corresponding hollow shape on the base layer and deposits two metals in the template. A protective layer is applied to the part where the metal is not deposited. The microcrack strain sensor prepared in this way has a higher precision crack and does not affect the service life of the crack during the strain process. However, the existing microcrack strain sensor has an essential defect, that is, the microcrack structure will be irreversibly damaged under large strain, so it is difficult to apply to complex practical application environments. Summary of the invention

[0005] To this end, the purpose of the present invention is to provide a new type of microcrack strain sensor with better strain sensing performance under lower strain and good environmental adaptability in view of the problems existing in the prior art.

[0006] The present invention is achieved through the following technical solutions:

[0007] A microcrack strain sensor comprises a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer; the raw material formula comprises, by weight: 50-90 parts of a flexible substrate material; 0-5 parts of an elastomer crosslinking agent; 0-10 parts of an elastomer crosslinking aid; 1-5 parts of a brittle film material; 0.01-0.5 parts of a conductive filler; and 0-3 parts of an interface modifier; the flexible substrate material is one or more of a thermosetting elastomer, a thermoplastic elastomer, and a flexible film; the brittle film material is one or more of carboxymethyl chitosan, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, ethylene-vinyl acetate copolymer, cellulose acetate, ethyl cellulose, polyacrylamide, polymethyl methacrylate, polyvinyl chloride, and polycarbonate; the conductive filler is one or more of carbon nanotubes, graphene, conductive carbon black, nanosilver wire, poly(3,4-ethylenedioxythiophene), polyacetylene, and polyaniline.

[0008] Further preferably, the thermosetting elastomer is one or more of natural rubber, natural rubber latex, epoxidized natural rubber, epoxidized natural rubber latex, ethylene-propylene rubber, silicone rubber, fluororubber, nitrile rubber, nitrile rubber latex, carboxylated nitrile rubber latex, styrene-butadiene rubber, styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, eucommia latex and dandelion latex, and the thermoplastic elastomer is one or more of styrene-butadiene block copolymer, ethylene-octene copolymer, polyurethane elastomer and polyamide elastomer.

[0009] Further preferably, the flexible film material is one or more of polyimide, polyester, cycloolefin polymer and liquid crystal polymer.

[0010] Further preferably, the elastomer crosslinking agent is one or more of a sulfur vulcanizing agent, a peroxide vulcanizing agent, a hydrosilylation crosslinking agent, an amine vulcanizing agent and a bisphenol vulcanizing agent.

[0011] Further preferably, the elastomer crosslinking aid is one or more of zinc oxide, thiazole accelerators, sulfonamide accelerators, thiuram accelerators, thioformate accelerators, guanidine accelerators, bisphenol accelerators, quaternary ammonium salt accelerators, quaternary phosphate salt accelerators, cyanurate accelerators and transition metal coordination accelerators.

[0012] Further preferably, the carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes; the conductive carbon black is one or more of oil furnace conductive carbon black, heavy oil recycled conductive carbon black and carbide acetylene conductive carbon black.

[0013] Further preferably, the interface modifier is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an aluminum-titanium composite coupling agent, an anionic surfactant, a cationic surfactant and a nonionic surfactant.

[0014] The present invention also provides a method for preparing the microcrack strain sensor, comprising the following steps:

[0015] a) obtaining a flexible substrate layer, wherein the flexible substrate layer is a flexible film or an elastomeric film, or a flexible film-elastomeric film composite flexible substrate layer; the preparation method of the elastomeric film is: sequentially adding an elastomer crosslinking agent, or an elastomer crosslinking agent and an elastomer crosslinking auxiliary agent, or an elastomer crosslinking agent, an elastomer crosslinking auxiliary agent and an interface modifier to a thermosetting elastomer latex, a thermosetting elastomer solution, or a thermoplastic elastomer solution, mixing them uniformly, and then molding to obtain the elastomeric film.

[0016] b) Preparation of crack layer of brittle conductive film, the method is as follows:

[0017] i) dissolving the brittle film material in a solvent to obtain a solution of the brittle film material.

[0018] ii) dispersing the conductive filler or the conductive filler and the interface modifier in the solution of the brittle film material under the action of ultrasound to obtain a conductive filler-brittle film material suspension.

[0019] iii) coating the conductive filler-brittle film material suspension obtained in step ii) on the surface of the flexible base layer in batches, and heating and drying the suspension to form a brittle conductive film layer on the surface of the flexible base layer.

[0020] iv) Pre-bending or stretching the brittle conductive film layer obtained in step iii) to form uniform cracks, thereby obtaining a brittle conductive film crack layer.

[0021] c) Repeat step a) to obtain a flexible substrate layer and cover the flexible substrate layer on the surface of the conductive film crack layer as a flexible encapsulation layer to seal the conductive film crack layer, thereby obtaining the microcrack strain sensor.

[0022] Further preferably, between step a) and step b), the flexible substrate layer is subjected to surface treatment, and the surface treatment method is one or more of electroplating, chemical plating, electrophoresis, chemical heat treatment, ozone, plasma and laser surface treatment. After step iv), a conductive copper sheet is introduced into the crack layer of the brittle conductive film as an output electrode, and after step c), the output electrode is led out of the flexible packaging layer.

[0023] Further preferably, the ultrasonic action time in step ii) is 0.1 to 2 hours, and the ultrasonic action power is 100 to 10000 W; the bending curvature radius in step iv) is 1 to 5 mm, and the stretching rate is 50 to 2000 cm / min.

[0024] Further preferably, the microcrack strain sensor prepared above is most sensitive to the strain in the plane caused by stretching or compression. For the strain perpendicular to or inclined at a certain angle to the microcrack strain sensor, such as pressing, the preparation method of the microcrack strain sensor can also add step d): fix the two ends of the microcrack strain sensor prepared in step c) and suspend it in the middle to obtain an arc-shaped microcrack strain sensor with an arc structure. This structure can convert the strain of the microcrack strain sensor in the vertical or inclined direction at a certain angle into the strain in the horizontal plane, so that the arc-shaped microcrack strain sensor has high sensitivity to the strain in the vertical or inclined direction at a certain angle.

[0025] Beneficial effects:

[0026] The microcrack strain sensor based on the flexible substrate layer-brittle conductive layer of the present invention has a GF value of up to 400000 or more. The strain response range of the microcrack strain sensor is adjustable (the minimum response strain is as low as 1%, and the maximum response strain is as high as 100%) to adapt to different application scenarios.

[0027] The micro-crack strain sensor based on the flexible substrate layer-brittle conductive layer of the present invention can still maintain better strain sensing performance after being subjected to large strain or cyclic strain, and has good stability.

[0028] The microcrack strain sensor based on the flexible substrate layer-brittle conductive layer of the present invention has a simple preparation process and is convenient for large-scale production. The prepared microcrack strain sensor is small in size and light in weight, and is suitable for wearable smart devices.

[0029] The microcrack strain sensor based on the flexible substrate layer-brittle conductive layer of the present invention has an extremely high GF value and an adjustable strain response range. Even at a very low voltage, it can still output a very large current change signal (when the working voltage is 1.5V, a significant change in current can be detected), so it is suitable for low-voltage environments, improves the safety of the strain sensor, and reduces the energy consumption of the strain sensor. It is suitable for wearable smart devices, aerospace and other fields in low-voltage environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the structure of a microcrack strain sensor provided in Example 10;

[0031] Figure 2 A schematic diagram of the structure and working principle of the arc-shaped microcrack sensor provided by the present invention;

[0032] Figure 3 It is a working principle diagram of the microcrack strain sensor of the present invention;

[0033] Figure 4 a) is a scanning electron microscope image of the initial state of the crack layer of the brittle conductive film of the microcrack strain sensor provided in Example 2;

[0034] Figure 4 b) is a scanning electron microscope image of the crack layer of the brittle conductive film of the microcrack strain sensor provided in Example 2 at 50% strain;

[0035] Figure 5 3D scanning cross-sectional curves of the microcrack strain sensor of Example 4 under different strains: a) 0% strain; b) 5% strain; c) 50% strain; d) an enlarged view of Figure c);

[0036] Figure 63D scanning diagram of the microcrack strain sensor of Example 4 under different strains;

[0037] Figure 7 The resistance change rate-strain curve diagram of the microcrack strain sensor of Example 9;

[0038] Figure 8 a) with Figure 8 b) are resistivity variation curves of the microcrack strain sensor of Example 5 under 50% and 100% cyclic strain. DETAILED DESCRIPTION

[0039] In order to better understand the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, it should be noted that the embodiments do not constitute a limitation on the scope of protection claimed for the present invention.

[0040] The present invention provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer; the raw material formula thereof comprises, by weight: 50 to 90 parts of a flexible substrate material, 0 to 5 parts of an elastomer crosslinking agent, 0 to 10 parts of an elastomer crosslinking aid, 1 to 5 parts of a brittle film material, 0.01 to 0.5 parts of a conductive filler and 0 to 3 parts of an interface modifier.

[0041] The flexible substrate material is one or more of a thermosetting elastomer, a thermoplastic elastomer, and a flexible film; the brittle film material is one or more of carboxymethyl chitosan, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, ethylene-vinyl acetate copolymer, cellulose acetate, ethyl cellulose, polyacrylamide, polymethyl methacrylate, polyvinyl chloride, and polycarbonate; the conductive filler is one or more of carbon nanotubes, graphene, conductive carbon black, nanosilver wire, poly(3,4-ethylenedioxythiophene), polyacetylene, and polyaniline; the thermosetting elastomer is one or more of natural rubber, natural rubber latex, epoxidized natural rubber, epoxidized natural rubber latex, ethylene-propylene rubber, silicone rubber, fluororubber, nitrile rubber, nitrile rubber latex, carboxylated nitrile rubber latex, styrene-butadiene rubber, styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, eucommia latex, and dandelion latex; the thermoplastic elastomer is one or more of styrene-butadiene block copolymer, ethylene-octene copolymer, polyurethane elastomer, and polyamide elastomer.

[0042] The material of the flexible film is one or more of polyimide, polyester, cycloolefin polymer and liquid crystal polymer.

[0043] The elastomer crosslinking agent is one or more of a sulfur vulcanizing agent, a peroxide vulcanizing agent, a hydrosilylation crosslinking agent, an amine vulcanizing agent and a bisphenol vulcanizing agent.

[0044] The elastomer crosslinking aid is one or more of zinc oxide, thiazole accelerators, sulfonamide accelerators, thiuram accelerators, thioformate accelerators, guanidine accelerators, bisphenol accelerators, quaternary ammonium salt accelerators, quaternary phosphate salt accelerators, cyanurate accelerators and transition metal coordination accelerators.

[0045] The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes; the conductive carbon black is one or more of oil furnace conductive carbon black, heavy oil reproducible conductive carbon black and calcium carbide acetylene conductive carbon black.

[0046] The interface modifier is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an aluminum-titanium composite coupling agent, an anionic surfactant, a cationic surfactant and a nonionic surfactant.

[0047] The present invention also provides a method for preparing the microcrack strain sensor, comprising the following steps:

[0048] a) obtaining a flexible substrate layer, wherein the flexible substrate layer is a flexible film or an elastomeric film, or a flexible film-elastomeric film composite flexible substrate layer; the preparation method of the elastomeric film is: sequentially adding an elastomer crosslinking agent, or an elastomer crosslinking agent and an elastomer crosslinking auxiliary agent, or an elastomer crosslinking agent, an elastomer crosslinking auxiliary agent and an interface modifier to a thermosetting elastomer latex or a thermosetting elastomer solution or a thermoplastic elastomer solution, mixing them evenly, and then molding to obtain the elastomeric film. That is, in some embodiments, a commercially available flexible film is used as the flexible substrate layer, an elastomeric film can also be used as the flexible substrate layer, or a laminated flexible film and an elastomeric film can constitute a flexible film-elastomeric film composite flexible substrate layer as the flexible substrate layer.

[0049] b) Preparation of crack layer of brittle conductive film, the method is as follows:

[0050] i) dissolving the brittle film material in a solvent to obtain a solution of the brittle film material.

[0051] ii) dispersing the conductive filler or the conductive filler and the interface modifier in the solution of the brittle film material under the action of ultrasound to obtain a conductive filler-brittle film material suspension.

[0052] iii) coating the solution in ii) on the surface of the flexible base layer in batches, and heating and drying the layer to form a brittle conductive film layer on the surface of the flexible base layer.

[0053] iv) forming uniform cracks on the brittle conductive film layer in iii) by bending or stretching to obtain a brittle conductive film crack layer.

[0054] c) Repeat step a) to obtain a flexible substrate layer and cover the flexible substrate layer on the surface of the conductive film crack layer as a flexible encapsulation layer to seal the conductive film crack layer, thereby obtaining the microcrack strain sensor.

[0055] In some embodiments, between step a) and step b), the flexible substrate layer is subjected to surface treatment, and the surface treatment method is one or more of electroplating / chemical plating, electrophoresis, chemical heat treatment, ozone, plasma and laser surface treatment. After step iv), a conductive copper sheet is introduced into the crack layer of the brittle conductive film as an output electrode, and after step c), the output electrode is led out of the flexible packaging layer.

[0056] Further preferably, the ultrasonic action time in step ii) is 0.1 to 2 hours, and the ultrasonic action power is 100 to 10000 W; the bending curvature radius in step iv) is 1 to 5 mm, and the stretching rate is 50 to 2000 cm / min.

[0057] The microcrack strain sensor prepared as described above may be a stacked strip sensor, which can respond to strains in any direction, and is particularly sensitive to strains in the horizontal plane caused by stretching or compression, but is relatively less sensitive to strains such as pressing that are perpendicular to or inclined at a certain angle to the microcrack strain sensor. Therefore, further, for strains such as pressing the microcrack strain sensor in the vertical direction, the preparation method of the microcrack strain sensor may further add step d): fixing the two ends of the microcrack strain sensor prepared in step c) and suspending it in the middle to obtain an arc-shaped microcrack strain sensor. This structure can convert the strains perpendicular to or at a certain angle to the arc-shaped microcrack strain sensor into strains in the horizontal plane, thereby improving the sensitivity of the microcrack strain sensor to strains perpendicular to or at a certain angle. The working principle of the arc-shaped microcrack strain sensor when subjected to vertical strains such as pressing is as follows: Figure 2 Similarly, when the arc-shaped microcrack strain sensor is pressed at a certain tilt angle, the arc-shaped microcrack strain sensor can also convert the strain in the tilt direction into the strain in the horizontal plane, so the arc-shaped microcrack strain sensor can also improve the sensitivity to the strain in the tilt direction.

[0058] Example 1

[0059] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0060] Epoxidized natural rubber latex with an epoxidation degree of 30% was selected as a flexible substrate material, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan, and the conductive filler was single-walled carbon nanotubes. 2phr of sulfur, 1phr of ZDEC, and 0.5phr of zinc oxide were added to the epoxidized natural rubber latex, and the latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the latex to obtain an epoxidized natural rubber latex containing a vulcanization system. 2g of the epoxidized natural rubber latex containing a vulcanization system was added to a 30cm*30cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in an 80°C oven for drying and vulcanization for 2h to obtain a flexible substrate layer. Dissolve 0.1g of carboxymethyl chitosan in 10ml of deionized water, add 0.001g of single-walled carbon nanotubes (single-walled carbon nanotubes are 1% of the mass of carboxymethyl chitosan), and ultrasonically treat for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. Add the suspension into a polytetrafluoroethylene mold in 4 times, and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks are made by pre-bending (radius of curvature is 1mm) to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of epoxidized natural rubber latex containing a vulcanization system into the mold, dry it at 80°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and the output electrode is led out of the flexible encapsulation layer.

[0061] Example 2

[0062] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0063] Epoxidized natural rubber latex with an epoxidation degree of 10% was selected as a flexible substrate material, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan, and the conductive filler was single-walled carbon nanotubes. 2phr of sulfur, 1phr of ZDEC, and 0.5phr of zinc oxide were added to the epoxidized natural rubber latex, and the latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the latex to obtain an epoxidized natural rubber latex containing a vulcanization system. 2g of the epoxidized natural rubber latex containing a vulcanization system was added to a 20cm*20cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in an 80°C oven for drying and vulcanization for 2h to obtain a flexible substrate layer. Dissolve 0.1g of carboxymethyl chitosan in 10ml of deionized water, add 0.001g of single-walled carbon nanotubes (single-walled carbon nanotubes are 1% of the mass of carboxymethyl chitosan), and ultrasonically treat for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. Add the suspension to the mold in 4 times and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Pre-bending (radius of curvature is 1mm) is used to make microcracks to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of epoxidized natural rubber latex containing a vulcanization system to the mold, dry it at 80°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and lead the output electrode out of the flexible encapsulation layer.

[0064] Example 3

[0065] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0066] A carboxylated styrene butadiene rubber latex with a carboxyl content of 1% was selected as a flexible substrate material, an elastomer crosslinking agent was sulfur, an elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), a brittle film material was carboxymethyl chitosan, and a conductive filler was single-walled carbon nanotubes. 2phr of sulfur, 1phr of ZDEC, and 0.5phr of zinc oxide were added to the carboxylated styrene butadiene rubber latex, and the latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the latex to obtain a carboxylated styrene butadiene rubber latex containing a vulcanization system. 2g of the carboxylated styrene butadiene rubber latex containing a vulcanization system was added to a 30cm*30cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in an 80°C oven for drying and vulcanization for 2h to obtain a flexible substrate layer. Dissolve 0.1g of carboxymethyl chitosan in 10ml of deionized water, add 0.001g of single-walled carbon nanotubes (single-walled carbon nanotubes are 1% of the mass of carboxymethyl chitosan), and ultrasonically treat for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. Add the suspension to the mold in 4 times and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Pre-bending (radius of curvature is 1mm) is used to make microcracks to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of carboxyl styrene-butadiene rubber latex containing a vulcanization system to the mold, dry it at 80°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and lead the output electrode out of the flexible encapsulation layer.

[0067] Example 4

[0068] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0069] Epoxidized natural rubber latex with an epoxidation degree of 30% was selected as a flexible substrate material, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was sodium carboxymethyl cellulose, and the conductive filler was single-walled carbon nanotubes. 2phr of sulfur, 1phr of ZDEC, and 0.5phr of zinc oxide were added to the epoxidized natural rubber latex, and the latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the latex to obtain an epoxidized natural rubber latex containing a vulcanization system. 2g of the epoxidized natural rubber latex containing a vulcanization system was added to a 10cm*10cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in an 80°C oven for drying and vulcanization for 2h to obtain a flexible substrate layer. Dissolve 0.1g sodium carboxymethyl cellulose in 10ml deionized water, add 0.001g single-walled carbon nanotubes (single-walled carbon nanotubes are 1% of the mass of sodium carboxymethyl cellulose), and ultrasonically treat for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. Add the suspension to the mold in 4 times and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Pre-bending (radius of curvature is 1mm) is used to make microcracks to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of epoxidized natural rubber latex containing a vulcanization system to the mold, dry it at 80°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and lead the output electrode out of the flexible encapsulation layer.

[0070] Example 5

[0071] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0072] Epoxidized natural rubber latex with an epoxidation degree of 30% was selected as a flexible substrate material, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan, and the conductive filler was single-walled carbon nanotubes. 2phr of sulfur, 1phr of ZDEC, and 0.5phr of zinc oxide were added to the epoxidized natural rubber latex, and the latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the latex to obtain an epoxidized natural rubber latex containing a vulcanization system. 2g of the epoxidized natural rubber latex containing a vulcanization system was added to a 6cm*6cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in an 80°C oven for drying and vulcanization for 2h to obtain a flexible substrate layer. Dissolve 0.1g of carboxymethyl chitosan in 10ml of deionized water, add 0.01g of poly(3,4-ethylenedioxythiophene) (poly(3,4-ethylenedioxythiophene) is 10% of the mass of carboxymethyl chitosan), and ultrasonically treat for 0.5h to obtain a uniformly dispersed poly(3,4-ethylenedioxythiophene) suspension. Add the suspension to the mold in 4 times and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks are made by pre-bending (radius of curvature is 1mm) to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of epoxidized natural rubber latex containing a vulcanization system to the mold, dry it at 80°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and lead the output electrode out of the flexible encapsulation layer.

[0073] Example 6

[0074] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0075] Silicone rubber was selected as the flexible base material, the elastomer crosslinker was diisopropylbenzene peroxide, the brittle film material was carboxymethyl chitosan, and the conductive filler was nanosilver wire. The silicone rubber was dissolved in dichloromethane solvent, and 2phr of the elastomer crosslinker diisopropylbenzene peroxide was added to make it evenly dispersed in the silicone rubber solution to obtain a silicone rubber solution containing a vulcanization system. 2g of the silicone rubber solution containing a vulcanization system was added to a 6cm*6cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in a 160°C oven to dry and vulcanize for 2h to obtain a flexible base layer. 0.1g of carboxymethyl chitosan was dissolved in 10ml of deionized water, and 0.001g of nanosilver wire (nanosilver wire was 1% of the mass of carboxymethyl chitosan) was added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed nanosilver wire suspension. The suspension was added to the mold in 4 times, and dried in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks were created by pre-bending (radius of curvature was 1 mm) to obtain a brittle conductive film crack layer, and a conductive copper sheet was introduced into the brittle conductive film crack layer as an output electrode. 1 g of a silicone rubber solution containing a vulcanization system was added to the mold, dried at 160°C, and vulcanized for 2 hours as a flexible encapsulation layer to seal the conductive film crack layer, and the output electrode was led out of the flexible encapsulation layer.

[0076] Example 7

[0077] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0078] Carboxylated nitrile rubber was selected as the flexible substrate material, the elastomer crosslinker was diisopropylbenzene peroxide, the brittle film material was carboxymethyl chitosan, the conductive filler was polyaniline, and the interface modifier was the silane coupling agent bis-[3-(triethoxysilyl)propyl]-tetrasulfide (TESPT). The carboxylated nitrile rubber was dissolved in a solvent, and 2phr of diisopropylbenzene peroxide was added. The solution was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system in the carboxylated nitrile rubber solution to obtain a carboxylated nitrile rubber solution containing the vulcanization system. 2g of the carboxylated nitrile rubber solution containing the vulcanization system was added to a 6cm*6cm*2cm polytetrafluoroethylene mold to spread it evenly. The mold was placed in a 160℃ oven for drying and vulcanization for 2h to obtain a flexible substrate layer. The flexible substrate layer was surface treated using TESPT. Dissolve 0.1g of carboxymethyl chitosan in 100ml of dimethylformamide (DMF), add 0.01g of polyaniline (polyaniline is 10% of the mass of carboxymethyl chitosan), and ultrasonically treat for 0.5h to obtain a polyaniline-carboxymethyl chitosan solution. Add the solution to the mold in 4 times, and dry it in an oven at 60°C for 8h to obtain a brittle conductive film layer. Pre-bending (radius of curvature is 1mm) is used to create microcracks to obtain a brittle conductive film crack layer, and a conductive copper sheet is introduced into the brittle conductive film crack layer as an output electrode. Add 1g of carboxyl nitrile rubber solution containing a vulcanization system to the mold, dry it at 160°C, and vulcanize it for 2h as a flexible encapsulation layer to close the conductive film crack layer, and lead the output electrode out of the flexible encapsulation layer.

[0079] Example 8

[0080] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0081] A commercial polyester film was selected as the flexible substrate layer, the brittle film material was polyacrylamide, and the conductive filler was single-walled carbon nanotubes. 0.1g of polyacrylamide was dissolved in 10ml of deionized water, and 0.001g of single-walled carbon nanotubes (single-walled carbon nanotubes were 1% of the mass of polyacrylamide) was added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. The suspension was sprayed on the surface of the polyester film 4 times, and dried in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks were created by pre-stretching (stretching rate of 500mm / min) to obtain a brittle conductive film crack layer, and a conductive copper sheet was introduced into the brittle conductive film crack layer as an output electrode. The polyester film was covered on the surface of the brittle conductive film crack layer as a flexible encapsulation layer to close the conductive film crack layer, and the output electrode was led out of the flexible encapsulation layer.

[0082] Example 9

[0083] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0084] A commercial polyimide film was selected as the flexible substrate layer, the brittle film material was cellulose acetate, the conductive filler was multi-walled carbon nanotubes, and the interface modifier was anionic surfactant sodium dodecylbenzene sulfonate. First, the polyimide film was surface treated with sodium dodecylbenzene sulfonate. 0.1g of cellulose acetate was dissolved in 10ml of deionized water, and 0.002g of multi-walled carbon nanotubes (multi-walled carbon nanotubes were 2% of the mass of polyacrylamide) was added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed multi-walled carbon nanotube suspension. The suspension was sprayed on the surface of the polyester film 4 times, and dried in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks were made by pre-stretching (stretching rate of 500mm / min) to obtain a brittle conductive film crack layer, and a conductive copper sheet was introduced into the brittle conductive film crack layer as an output electrode. The surface-treated polyester film was covered on the surface of the brittle conductive film crack layer as a flexible encapsulation layer to close the conductive film crack layer, and the output electrode was led out of the flexible encapsulation layer.

[0085] Example 10

[0086] This embodiment provides a microcrack strain sensor, such as Figure 1 As shown, it includes a flexible substrate layer 1, a brittle conductive film crack layer 2 and a flexible packaging layer 3 stacked from bottom to top, and the flexible substrate layer 1 includes a flexible film layer 11 and an elastic film layer 12 stacked from bottom to top, as shown in FIG. Figure 3 As shown, the brittle conductive film crack layer includes a body layer 21 and a transition layer 22, the flexible packaging layer 3 includes an elastic film packaging layer 31 and a flexible film packaging layer 32 stacked from bottom to top, and the microcrack strain sensor preparation method is as follows:

[0087] Epoxidized natural rubber latex with an epoxidation degree of 30% and polyimide film were selected as flexible substrate materials, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan, the conductive filler was single-walled carbon nanotubes, and the interface modifier was silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570). 2phr of sulfur, 1phr of ZDEC, 0.5phr of zinc oxide, and 2phr of KH570 were added to the epoxidized natural rubber latex. The latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system and the interface modifier in the latex to obtain the epoxidized natural rubber latex containing the vulcanization system and the interface modifier. 2g of epoxidized natural rubber latex containing a vulcanization system and an interfacial modifier was coated on the surface of a polyimide film and placed in an oven at 80°C for drying and vulcanization for 2h to obtain a flexible film layer 11 and an elastomer film layer 12 stacked from bottom to top as a flexible substrate layer 1. The upper surface of the flexible substrate layer was electroplated. 0.1g of carboxymethyl chitosan was dissolved in 10ml of deionized water, and 0.001g of single-walled carbon nanotubes (single-walled carbon nanotubes were 1% of the mass of carboxymethyl chitosan) and 1phr of KH570 were added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension. The suspension was added to the mold in 4 times and dried in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks were made by pre-bending (radius of curvature was 1mm) to obtain a brittle conductive film crack layer 2, and a conductive copper sheet was introduced into the brittle conductive film crack layer 2 as an output electrode (not shown). And 1g of epoxidized natural rubber latex containing a vulcanization system and an interface modifier is coated on the surface of the polyimide film and placed in an oven for drying at 80°C and vulcanization for 2h to obtain a polyimide film-epoxidized natural rubber latex film composite layer, and the polyimide film-epoxidized natural rubber latex film composite layer is covered on the brittle conductive film crack layer 2 as a flexible encapsulation layer 3 to close the conductive film crack layer, the epoxidized natural rubber latex film layer is bonded to the brittle conductive film crack layer, and the output electrode is led out of the flexible encapsulation layer.

[0088] Embodiment 11

[0089] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0090] Epoxidized natural rubber latex with an epoxidation degree of 30% and polyimide film were selected as flexible substrate materials, the elastomer crosslinking agent was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan and polycarbonate, the conductive filler was single-walled carbon nanotubes, and the interface modifier was silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570). 2phr of sulfur, 1phr of ZDEC, 0.5phr of zinc oxide, and 2phr of KH570 were added to the epoxidized natural rubber latex. The latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system and the interface modifier in the latex to obtain the epoxidized natural rubber latex containing the vulcanization system and the interface modifier. 2g of epoxidized natural rubber latex containing a vulcanization system and an interfacial modifier was coated on the surface of a polyimide film and placed in an oven at 80°C for drying and vulcanization for 2h to obtain a flexible substrate layer. The surface of the flexible substrate layer was electroplated. 0.05g of carboxymethyl chitosan was dissolved in 10ml of deionized water, and 0.0005g of single-walled carbon nanotubes (single-walled carbon nanotubes were 1% of the mass of carboxymethyl chitosan) and 1phr of KH570 were added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension, and the suspension was added to a mold twice for drying. 0.05g of polycarbonate was dissolved in 20ml of dichloromethane, and 0.0005g of single-walled carbon nanotubes (single-walled carbon nanotubes were 1% of the mass of polycarbonate) and 1phr of KH570 were added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed single-walled carbon nanotube suspension, and the suspension was added to a mold twice for drying. The oven temperature was 60°C and dried for 8 hours to obtain a composite brittle conductive film layer. Microcracks were made by pre-bending (radius of curvature was 1 mm) to obtain a brittle conductive film crack layer, and a conductive copper sheet was introduced into the brittle conductive film crack layer as an output electrode. 1g of epoxidized natural rubber latex containing a vulcanization system and an interface modifier was coated on the surface of the polyimide film and placed in an oven at 80°C for drying and vulcanization for 2 hours to obtain a polyimide film-epoxidized natural rubber latex film composite layer, and the polyimide film-epoxidized natural rubber latex film composite layer was covered on the brittle conductive film crack layer as a flexible encapsulation layer to close the conductive film crack layer, and the epoxidized natural rubber latex film layer was bonded to the brittle conductive film crack layer, and the output electrode was led out of the flexible encapsulation layer.

[0091] Example 12

[0092] This embodiment provides a microcrack strain sensor, comprising a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer stacked in sequence from bottom to top, and the preparation method thereof is as follows:

[0093] Epoxidized natural rubber latex with an epoxidation degree of 30% and polyimide film were selected as flexible substrate materials, the elastomer crosslinker was sulfur, the elastomer crosslinking aid was zinc oxide and zinc diethyldithiocarbamate (ZDEC), the brittle film material was carboxymethyl chitosan, the conductive filler was single-walled carbon nanotubes and poly (3,4-ethylenedioxythiophene), and the interface modifier was silane coupling agent γ-methacryloxypropyl trimethoxysilane (KH570). 2phr of sulfur, 1phr of ZDEC, 0.5phr of zinc oxide, and 2phr of KH570 were added to the epoxidized natural rubber latex. The latex was ultrasonically treated for 0.5h using an ultrasonic device to uniformly disperse the vulcanization system and the interface modifier in the latex to obtain an epoxidized natural rubber latex containing the vulcanization system and the interface modifier. 2g of epoxidized natural rubber latex containing a vulcanization system and an interfacial modifier was coated on the surface of a polyimide film and placed in an oven at 80°C for drying and vulcanization for 2h to obtain a flexible substrate layer. The surface of the flexible substrate layer was electroplated. 0.1g of carboxymethyl chitosan was dissolved in 10ml of deionized water, and 0.001g of single-walled carbon nanotubes and 0.001g of poly(3,4-ethylenedioxythiophene) (single-walled carbon nanotubes and poly(3,4-ethylenedioxythiophene) were both 1% of the mass of carboxymethyl chitosan) and 1phr of KH570 were added, and ultrasonic treatment was performed for 0.5h to obtain a uniformly dispersed suspension. The suspension was added to the mold in 4 times and dried in an oven at 60°C for 8h to obtain a brittle conductive film layer. Microcracks were made by pre-bending (radius of curvature was 1mm) to obtain a brittle conductive film crack layer, and a conductive copper sheet was introduced into the brittle conductive film crack layer as an output electrode. 1 g of epoxidized natural rubber latex containing a vulcanization system and an interface modifier is coated on the surface of a polyimide film and placed in an oven for drying at 80°C and vulcanization for 2 hours to obtain a polyimide film-epoxidized natural rubber latex film composite layer; the polyimide film-epoxidized natural rubber latex film composite layer is covered on the brittle conductive film crack layer as a flexible encapsulation layer to close the conductive film crack layer; the epoxidized natural rubber latex film layer is bonded to the brittle conductive film crack layer, and the output electrode is led out of the flexible encapsulation layer.

[0094] Comparative Example 1

[0095] The epoxy natural rubber latex with an epoxy degree of 30% is selected as the matrix, the elastomer crosslinking agent is sulfur, the elastomer crosslinking aid is zinc oxide and zinc diethyldithiocarbamate (ZDEC), and the conductive filler is single-walled carbon nanotubes. 0.05g of single-walled carbon nanotubes are added to 100ml of deionized water; the single-walled carbon nanotube suspension is ultrasonically treated for 0.5h using an ultrasonic device to obtain a uniformly dispersed single-walled carbon nanotube suspension; the suspension is added to 5g of epoxy natural rubber latex and ultrasonically treated for 0.5h to uniformly disperse the single-walled carbon nanotubes between the latex particles; the obtained suspension is placed in an oven at 60°C for drying and vulcanization for 24h to obtain an epoxy natural rubber / single-walled carbon nanotube composite material with an isolated structure.

[0096] A series of performance tests were performed on the microcrack strain sensors of Examples 1 to 12 and the epoxidized natural rubber / single-walled carbon nanotube composite material of Comparative Example 1. The performance test methods are as follows:

[0097] First, the prepared sample is cut into dumbbell-shaped splines with a cutter. Then, the splines are fixed with a clamp on the rubber tensile machine. Finally, the electrodes at both ends of the splines are connected to a multimeter. The resistance change of the splines is measured during the stretching process.

[0098] In the tensile test, the stretching rate of the spline is 10 mm / min; in the cyclic tensile test, the stretching rate and recovery rate of the spline are both 10 mm / min, and the maximum strain is 50% and 100% respectively. The multimeter selects the two-wire resistance mode, and the frequency of resistance measurement is 40 times / second.

[0099] The performance data of the microcrack strain sensors of Examples 1 to 12 and the epoxidized natural rubber / single-walled carbon nanotube composite material of Comparative Example 1 are shown in Table 1.

[0100] Table 1 Performance data of the microcrack strain sensors of Examples 1 to 12 and the epoxidized natural rubber / single-walled carbon nanotube composite material of Comparative Example 1

[0101] GF value Strain response range (%) Comparative Example 1 20 50-200 Example 1 450000 5-30 Example 2 260000 5-50 Example 3 130000 20-100 Example 4 120000 10-50 Example 5 40000 50-100 Example 6 50000 20-50 Example 7 200000 5-20 Example 8 100000 1-5 Example 9 120000 1-5 Example 10 150000 2-10 Embodiment 11 200000 2-20 Example 12 180000 5-10

[0102] The properties of Examples 1 to 12 are shown in Table 1. The Example numbers in the table correspond to the above-mentioned Examples.

[0103] Comparing Comparative Example 1 with Example 1, the microcrack strain sensor based on the flexible substrate layer-brittle conductive layer of the present invention has a higher GF value and a lower strain response range than the traditional conductive composite material strain sensor.

[0104] Comparing Example 1 and Example 2, using epoxidized natural rubber latex with different epoxidation degrees as the flexible substrate layer has a significant effect on the interaction between the flexible substrate layer and the crack layer of the brittle conductive film, thereby affecting the GF value and the strain response range.

[0105] Comparing Example 1 with Example 3, different elastomeric films are selected as the flexible base layer; comparing Example 1 with Example 4, different brittle film materials are selected; comparing Example 1 with Example 5, different conductive fillers are selected; comparing Example 1 with Example 6, different elastomeric films are selected as the flexible base layer and different conductive fillers are selected, and better strain sensing performance can be obtained.

[0106] Comparing Example 1 and Example 8, different flexible substrate materials are selected as the substrate layer, and the strain response range of the strain sensor is significantly different - when the flexible substrate layer is an elastomeric film, a large strain is required to achieve a sudden change in resistance; when the flexible substrate layer is a commercial flexible film, a small strain can achieve a sudden change in resistance. In actual application, the substrate layer can be flexibly selected according to the applicable environment.

[0107] Comparing Example 8 and Example 9, after the surface of the commercial flexible film is surface treated, the interface interaction between the flexible substrate layer and the crack layer of the brittle conductive film is improved, the thickness of the transition layer is increased, and the GF value is thereby improved.

[0108] Comparing Example 10 with Example 1, a flexible film-elastic film composite is selected as the flexible substrate layer, and the strain sensor has good strain sensing performance and can be applied to fields such as touch screens.

[0109] Comparing Example 10 with Example 11, different brittle conductive films are selected to compositely form a multi-layer brittle conductive film crack layer, which can effectively expand the strain response range.

[0110] Comparing Example 10 and Example 12, selecting different types of conductive fillers for compounding can effectively reduce the pre-mutation resistance and thus effectively increase the GF value.

[0111] Figure 1 This is a schematic diagram of the structure of the microcrack strain sensor obtained in Example 10, which consists of three parts: a flexible substrate layer, a brittle conductive film crack layer, and a flexible packaging layer. Electrical signal output can be achieved by introducing electrodes.

[0112] Figure 2 The schematic diagram of the working principle of the arc-shaped microcrack strain sensor provided by the present invention under vertical strain. When the arc-shaped microcrack strain sensor is vertically pressed, the vertical strain of the arc-shaped microcrack strain sensor is converted into strain in the horizontal plane.

[0113] Figure 3This is the working principle diagram of the microcrack strain sensor of the present invention. For tensile strain, in the initial state, the cracks in the crack layer of the brittle conductive film are basically in a closed state; when tensile strain is applied to the microcrack strain sensor, the cracks in the crack layer of the brittle conductive film gradually expand, and the resistance increases sharply; when the strain is removed, the cracks gradually disappear, and the resistance decreases. For compressive strain, in the initial state, the microcrack strain sensor is in a pre-stretched state, and the cracks in the crack layer of the brittle conductive film are in an extended state; when a certain compressive strain is applied to the microcrack strain sensor, the cracks in the crack layer of the brittle conductive film gradually close, and the resistance decreases sharply; when the strain is removed, the cracks gradually recover, and the resistance increases.

[0114] Figure 4 a) is a scanning electron microscope image of the initial state of the crack layer of the brittle conductive film of the microcrack strain sensor obtained in Example 2. Compared with the flat and smooth surface of the conductive film, there are obvious wrinkles at the crack; Figure 4 b) is a scanning electron microscope image of the crack layer of the brittle conductive film in Example 2 at 50% strain. It can be clearly seen that the crack propagation modes of the main layer 21 and the transition layer 22 of the crack layer of the brittle conductive film are obviously different.

[0115] Figure 5 a) is a 3D scanning cross-sectional curve of the initial state of the microcrack strain sensor obtained in Example 4, the width of the microcrack is 9.1 μm and the depth is 5.6 μm; Figure 5 b) is a 3D scanning cross-sectional curve of the microcrack strain sensor based on the flexible substrate layer-brittle conductive layer when the strain is increased to 5%, and the width and depth of the microcrack are increased to 23.9μm and 15.7μm respectively; Figure 5 c) is the 3D scanning cross-sectional curve of the microcrack strain sensor based on the flexible substrate layer-brittle conductive layer when the strain is increased to 50%. The width and depth of the microcrack are increased to 188.1 μm and 24.6 μm respectively, and cracks appear in the transition layer at this time. Figure 5 d shows that the crack depth of the transition layer is about 1.5 μm (ie, the depth of the transition layer 22).

[0116] Figure 6 The three-dimensional scanning images of the microcrack strain sensor obtained in Example 4 under different strains show that the crack width and depth both increase with increasing strain.

[0117] Figure 7 The resistance change rate-strain curve of the microcrack strain sensor obtained in Example 9 shows that the resistance change rate increases sharply with the increase of strain. When the strain is 5%, the resistance change rate is as high as 40,000.

[0118] Figure 8 a) with Figure 8b) are the resistivity change curves of the microcrack strain sensor obtained in Example 5 under 50% and 100% cyclic strain. The resistivity change is basically synchronized with the strain and does not decay with the increase in the number of cycles, indicating that the microcrack strain sensor based on the flexible substrate layer-brittle conductive layer has good durability.

[0119] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A microcrack strain sensor, characterized in that: It includes a flexible substrate layer, a brittle conductive film crack layer and a flexible packaging layer; in terms of mass fraction, the raw material formula of the microcrack strain sensor includes: 50~90 parts of flexible substrate material; Elastomer crosslinking agent 0~5 parts; Elastomer crosslinking agent 0-10 parts; 1~5 parts of brittle film material; Conductive filler 0.01~0.5 parts; Interface modifier 0~3 parts; The flexible substrate material is one or more of a thermosetting elastomer, a thermoplastic elastomer, and a flexible film; The brittle film material is one or more of carboxymethyl chitosan, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, ethylene-vinyl acetate copolymer, cellulose acetate, ethyl cellulose, polyacrylamide, polymethyl methacrylate, polyvinyl chloride and polycarbonate; The conductive filler is one or more of carbon nanotubes, graphene, conductive carbon black, nano silver wire, poly(3,4-ethylenedioxythiophene), polyacetylene, and polyaniline. Among them, the brittle film material and the conductive filler form a mixed liquid which is coated on the flexible substrate for multiple times to obtain a brittle conductive film layer. The brittle conductive film layer forms a brittle conductive film crack layer under various strains such as stretching, bending and pressing. The brittle conductive film crack layer is divided into a transition layer close to the flexible substrate layer and a main body layer away from the flexible substrate layer. The transition layer and the main body layer show different crack extension morphologies.

2. The microcrack strain sensor according to claim 1, characterized in that: The thermosetting elastomer is one or more of natural rubber, natural rubber latex, epoxidized natural rubber, epoxidized natural rubber latex, ethylene-propylene rubber, silicone rubber, fluororubber, nitrile rubber, nitrile rubber latex, carboxylated nitrile rubber latex, styrene-butadiene rubber, styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, eucommia latex and dandelion latex; the thermoplastic elastomer is one or more of styrene-butadiene block copolymer, ethylene-octene copolymer, polyurethane elastomer and polyamide elastomer; the material of the flexible film is one or more of polyimide, polyester, cycloolefin polymer and liquid crystal polymer.

3. The microcrack strain sensor according to claim 1, characterized in that: The elastomer crosslinking agent is one or more of a sulfur vulcanizing agent, a peroxide vulcanizing agent, a hydrosilylation crosslinking agent, an amine vulcanizing agent and a bisphenol vulcanizing agent.

4. The microcrack strain sensor according to claim 1, characterized in that: The elastomer crosslinking aid is one or more of zinc oxide, thiazole accelerators, sulfonamide accelerators, thiuram accelerators, thioformate accelerators, guanidine accelerators, bisphenol accelerators, quaternary ammonium salt accelerators, quaternary phosphate salt accelerators, cyanurate accelerators and transition metal coordination accelerators.

5. The microcrack strain sensor according to claim 1, characterized in that: The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes; the conductive carbon black is one or more of oil furnace conductive carbon black, heavy oil reproducible conductive carbon black and calcium carbide acetylene conductive carbon black.

6. The microcrack strain sensor according to claim 1, characterized in that: The interface modifier is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, an aluminum-titanium composite coupling agent, an anionic surfactant, a cationic surfactant and a nonionic surfactant.

7. A method for preparing a microcrack strain sensor, used for preparing the microcrack strain sensor according to any one of claims 1 to 6, characterized in that: The steps include: a) obtaining a flexible substrate layer, wherein the flexible substrate layer is a flexible film or an elastomeric film, or a flexible film-elastomeric film composite flexible substrate layer; the preparation method of the elastomeric film is: sequentially adding an elastomer crosslinking agent, or an elastomer crosslinking agent and an elastomer crosslinking auxiliary agent, or an elastomer crosslinking agent, an elastomer crosslinking auxiliary agent and an interface modifier to a thermosetting elastomer latex, a thermosetting elastomer solution, or a thermoplastic elastomer solution, mixing them uniformly, and then molding to obtain the elastomeric film; b) Preparation of crack layer of brittle conductive film, the method is as follows: i) dissolving the brittle film material in a solvent to obtain a solution of the brittle film material; ii) dispersing the conductive filler or the conductive filler and the interface modifier in a solution of the brittle film material under ultrasonic action to obtain a conductive filler-brittle film material suspension; iii) coating the conductive filler-brittle film material suspension obtained in step ii) on the surface of the flexible base layer in batches, and heating and drying to form a brittle conductive film layer on the surface of the flexible base layer; iv) forming uniform cracks on the brittle conductive film layer obtained in step iii) by bending or stretching to obtain a brittle conductive film crack layer; c) Repeat step a) to obtain a flexible substrate layer and cover the flexible substrate layer on the surface of the conductive film crack layer as a flexible encapsulation layer to seal the conductive film crack layer, thereby obtaining a microcrack strain sensor.

8. The method for preparing the microcrack strain sensor according to claim 7, characterized in that: Between step a) and step b), the method further includes surface treatment of the flexible substrate layer, and the surface treatment method is one or more of electroplating, chemical plating, electrophoresis, chemical heat treatment, ozone, plasma and laser surface treatment; after step iv), the method further includes introducing a conductive copper sheet into the crack layer of the brittle conductive film as an output electrode, and after step c), the method further includes leading the output electrode out of the flexible packaging layer.

9. The method for preparing the microcrack strain sensor according to claim 7, characterized in that: The ultrasonic action time in step ii) is 0.1-2 hours, and the ultrasonic action power is 100-10000 W; the bending curvature radius in step iv) is 1-5 mm, and the stretching rate is 50-2000 cm / min.

10. The method for preparing a microcrack strain sensor according to claim 7, characterized in that: Add step d): fix both ends of the microcrack strain sensor prepared in step c) and leave it suspended in the middle to form an arc-shaped microcrack strain sensor.

Citation Information

Patent Citations

  • Microcrack strain sensing element as well as preparation method and application thereof

    CN113310395A

  • Filling type flexible strain sensing material and preparation method thereof

    CN113930037A

  • Dynamically vulcanized polylactic acid plastic / rubber thermoplastic elastomer and preparation method thereof

    CN103642184A

  • Flexible strain sensor with crack structure and preparation method thereof

    CN105783697A

  • Strain sensor based on graphical induced cracks and preparation method of strain sensor

    CN111721192A